2011
DOI: 10.4061/2011/174135
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Awareness, Treatment, and Control of Hypertension among Saudi Adult Population: A National Survey

Abstract: This cross-sectional study aimed at estimating prevalence, awareness, treatment, control, and predictors of hypertension among Saudi adult population. Multistage stratified sampling was used to select 4758 adult participants. Three blood pressure measurements using an automatic sphygmomanometer, sociodemographics, and antihypertensive modalities were obtained. The overall prevalence of hypertension was 25.5%. Only 44.7% of hypertensives were aware, 71.8% of them received pharmacotherapy, and only 37.0% were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
125
5
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 41 publications
(49 reference statements)
18
125
5
7
Order By: Relevance
“…A prevalência de HAS foi de 25,7 (IC95%: 22,7-28,6), com maior predominância no sexo masculino (28,7; IC95%: 24,3-33,0) quando comparada à prevalência no sexo feminino (22,8;IC95%: 18,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)7). A prevalência de HAS apresentou tendência crescente ao longo das faixas etárias, com maior valor entre indivíduos com mais de 60 anos (58,6; IC95%: 49,6-67,4).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A prevalência de HAS foi de 25,7 (IC95%: 22,7-28,6), com maior predominância no sexo masculino (28,7; IC95%: 24,3-33,0) quando comparada à prevalência no sexo feminino (22,8;IC95%: 18,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)7). A prevalência de HAS apresentou tendência crescente ao longo das faixas etárias, com maior valor entre indivíduos com mais de 60 anos (58,6; IC95%: 49,6-67,4).…”
Section: Resultsunclassified
“…Em contraposição, as mulheres são mais preocupadas com estado de saúde e procuram mais assistência médica e, portanto, podem apresentar detecção precoce e maior controle da HAS quando comparadas aos homens 23 . Em nosso estudo, os fatores preditores para HAS foram distintos entre homens e mulheres.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…This study revealed the presence of particularly hypertension, coronary artery disease and retinopathy, as well as the corresponding use of insulin and medication to treat complications. Previous research confirmed that DM is a significant predictor of hypertension in the KSA (Saeed et al, 2011). Badran and Laher (2012) found 31% prevalence of retinopathy among type II diabetics in Arab speaking countries (N=4,758).…”
Section: Discussionmentioning
confidence: 54%
“…In the Gulf area, women are often over protected due to religious or cultural barriers and can't publicly participate in physical activity [4,5]. Sedentarism, smoking, energy-dense food as well as modifiable risk factors (dyslipidemia, diabetes mellitus (DM), arterial hypertension (HTN) [6,7] and obesity are strongly associated with cardiovascular diseases (CVD) risk.…”
Section: Introductionmentioning
confidence: 99%